A MALDI-TOF MS-based approach to improve group B Streptococcus screening among pregnant people in Brazil - Dr Tatiana Pinto; Debora Nery; Dr Laura Oliveira; Dr Natalia Costa; Prof Sergio Fracalanzza; Dr Ana Caroline Botelho; Prof Lucia Teixeira; Dr Penelope Marinho (International Journal of Infectious Diseases)
Introduction: Group B Streptococcus (GBS) is a leading agent of sepsis and meningitis in neonates. Prevention is made by screening pregnant women at 36-37 gestational weeks and applying intrapartum antibiotic prophylaxis (IAP). However, GBS colonization in pregnant women can be transient or intermittent. GBS-negative women at 36-37 gestational week may be GBS-positive at the moment of labor, and vice-versa. Culture-based techniques have a long turnaround-time (TAT), and the development of a cost-effective, reliable and fast screening method that could be applied just before labor can aid to antimicrobial stewardship. Here we propose a MALDI-TOF-based protocol for GBS detection directly in pre-enriched clinical samples. Methods: Anovaginal samples of 612 women attending a maternity in Rio de Janeiro, Brazil, between July 2019 and May 2021, were processed as follows. After pre-enriching clinical samples for 18h at 36°C, they were subcultured onto blood agar plates and beta-hemolytic colonies were identified by MALDI-TOF (Bruker Microflex LT). Direct detection of GBS from clinical samples by MALDI-TOF MS was performed with 1mL of the pre-enriched broth, which was centrifuged, washed and the resulting pellet applied onto the MALDI target. Results and Discussion: Among 612 samples tested, 65 were positive in culture (10.6%) and 50 (8.2%) were positive by the alternative MALDI-TOF approach. MALDI-TOF mainly failed to detect GBS when the resulting pellet did not contain the minimum detection limit of the equipment. In these cases, subculturing onto blood agar plates or increasing the incubation period improved detection. The number of total agreements was 597 (97.55% of the observations). The sensitivity and specificity of the proposed method were high (81% and 100% respectively). The Kappa coefficient was 0.856 with 95% of confidence interval. MALDI-TOF method was faster; while the mean TAT for culture was 48h, the TAT of MALDI-TOF detection was 19h. Conclusions: Our results suggest that detection of GBS directly in clinical samples using MALDI-TOF MS is a suitable, fast, and reliable alternative for GBS screening among pregnant women. Such approach can aid to antimicrobial stewardship and lead to reduced rates of neonatal sepsis and meningitis.